Flood countermeasure management in Bulak Banteng Surabaya - Mahtori, Mahtori Yuliyanto; Maschuri, Septiyan Ilfan Mahfudz; Khuluqi, Ahmad Hasan; Inova, Fitra Nawawi; Wibisono, Mochamad Djulianto (ASEAN Natural Disaster Mitigation and Education Journal, 2024)
The rainy season in Indonesia occurs due to the west monsoon wind blowing from the Asian continent which carries a lot of water vapor to the Australian continent due to climate change, it causes high rainfall and can potentially cause floods. In addition, the phenomenon of garbage accumulation in the river and the failure of the drainage system are the reasons for flooding in metropolitan cities, especially in Surabaya. This study aims to determine the preparedness of the community, especially the people of Bulak Banteng Village, in facing floods during the rainy season. Data were collected using the Simple Random Sample (SRS) method with 30 correspondents randomly selected at the research location. The results showed that many people were aware of the causes of flooding and the signs and impacts caused by flooding. Therefore, some people have prepared themselves in case of flooding by raising the floor of their houses so that water does not enter the house. In the event of a flood, the community prefers to evacuate themselves to a relative's place that is not affected by flooding rather than going to the disaster evacuation site provided by the local government, this happens because of the lack of training or socialization of flood response in the community, resulting in the lack of flood disaster information obtained by the community.